DESIGN OF DIGITAL IMAGE EDGE DETECTION APPLICATIONS USING FREI-CHEN ALGORITHM - Leonardus Sitinjak (Sean Institute, 2020)
One image processing technique used is edge detection. Edge detection is a common thing in digital image processing because it is one of the first steps in image segmentation, which aims to present the objects contained in the image. Edge detection functions to identify the boundary lines of an object against overlapping backgrounds. Currently several methods can be used for edge detection, for example the Sobel, Canny, Prewitt, Frei-Chen, and SUSAN methods. In this research, 1 method is taken, namely the Frei-Chen algorithm. The results of this study indicate that this operator is successful in detecting edges in an image. When detecting edges in images containing noise the Frei-Chen algorithm is better at edge detection.